2016
DOI: 10.1111/mpp.12426
|View full text |Cite
|
Sign up to set email alerts
|

Translationally controlled tumour protein (TCTP) from tomato and Nicotiana benthamiana is necessary for successful infection by a potyvirus

Abstract: Translationally controlled tumour protein (TCTP) is a ubiquitously distributed protein in eukaryotes, involved in the regulation of several processes, including cell cycle progression, cell growth, stress protection, apoptosis and maintenance of genomic integrity. Its expression is induced during the early stages of tomato (Solanum lycopersicum) infection by the potyvirus Pepper yellow mosaic virus (PepYMV, a close relative of Potato virus Y). Tomato TCTP is a protein of 168 amino acids, which contains all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…Of note, since TCTP is highly regulated at the translational level, its accumulation in these transgenic lines may vary significantly as already evidenced for AtTCTP1 in Arabidopsis (only 50% increase at the protein level despite a 13-fold increase in gene expression; Berkowitz et al 2008). Consistent with this, the severity of the phenotypic alterations associated with the silencing of SlTCTP in tomato was directly correlated with the efficiency of gene knockdown (Bruckner et al 2016). Alternatively, the additive effect of the endogenous NtTCTP on the growth of the SlTCTP-OE plants could be envisaged.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Of note, since TCTP is highly regulated at the translational level, its accumulation in these transgenic lines may vary significantly as already evidenced for AtTCTP1 in Arabidopsis (only 50% increase at the protein level despite a 13-fold increase in gene expression; Berkowitz et al 2008). Consistent with this, the severity of the phenotypic alterations associated with the silencing of SlTCTP in tomato was directly correlated with the efficiency of gene knockdown (Bruckner et al 2016). Alternatively, the additive effect of the endogenous NtTCTP on the growth of the SlTCTP-OE plants could be envisaged.…”
Section: Discussionsupporting
confidence: 72%
“…It should be emphasized that SlTCTP shows 80% amino acid identity with NtTCTP. Also noteworthy, some of the described phenotypic alterations caused by the silencing of SlTCTP in tomato, such as stunting, modified inflorescence habit and abnormal fruit morphology (Bruckner et al 2016), resemble ethylene-associated pleiotropic effects reported in tomato (Lin et al 2008). In addition, the fact that the SlTCTP-OE lines exhibited enhanced lateral root…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Emerging evidence suggests a role of plant TCTP in growth regulation and programmed cell death control ( Berkowitz et al, 2008 ; Toscano-morales et al, 2015 ; Chou et al, 2016 ). Plant TCTP was also recently found to respond to pathogen stress ( Li et al, 2010 ; Hinojosamoya et al, 2013 ; Bruckner et al, 2017 ). In our previous work, we found that TCTP (XP-004134215) was significantly differentially expressed between two sister cucumber lines (genotypes that were either highly resistant or highly susceptible to S. fuliginea ) by 2-D gel electrophoresis ( Fan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%